von Willebrand factor polymorphism (rs1063856) as a risk factor for portal vein thrombosis in chronic liver diseases - Isis Samy Bedira; Olfat M. Hendy; Moones Abdelaal; Ashraf A. Basuni; Asma Ebrahim Gaber Koshoo; Alzhraa Alkhatib; Sally S. Mandour (Egyptian Liver Journal)
Abstract Background Due to its well-established involvement in clot formation, von Willebrand factor (vWF) has been held responsible for decades as a risk factor for arterio-venous thrombosis. It is currently unclear how genetic differences in vWF genes relate to the incidence of portal vein thrombosis (PVT). Thus, the aim of this study was to evaluate the significance of vWF:Ag level and vWF gene polymorphism (rs1063856) as risk factors for PVT in patients with chronic liver disease (CLD). Subjects and methods This research of 70 individuals with CLD comprised 30 without PVT and 40 with PVT. Twenty patients with PVT-linked hepatocellular carcinoma (HCC) and 20 patients with non-HCC-PVT comprised the two subgroups from the 40 PVT patients. Additionally, 30 healthy volunteers of the same age and gender as the patients were included in the study as a control group. Tests for liver and renal function, coagulation profile, complete blood count, hepatitis virus markers, and vWF:Ag level were conducted. The identification of the vWF gene polymorphism (rs1063856) was assessed using real-time PCR. Results When comparing CLD patients with PVT to those without PVT and the healthy control group, there was a substantial rise in the vWF: Ag level. Additionally, compared to instances of benign PVT, the vWF:Ag levels were considerably greater in malignant PVT. CLD patients with PVT had higher frequencies of the vWF (rs1063856) AA genotype and A alleles (37.5% and 61.3%, respectively) than did control and non-PVT cases. Patients with the AA genotype showed the highest serum levels of vWF antigen, followed by those with the TA genotype. Conclusion vWF (rs1063856) AA gene polymorphism has a strong correlation with vWF plasma level and may be a risk factor for PVT development in CLD patients. These findings should be included in the risk assessment model to determine and guide management for those patients.